First-Line Nivolumab in Stage IV or Recurrent Non-Small-Cell Lung Cancer - Carbone, David P.; Reck, Martin; Steins, Martin (The New England journal of medicine, 2017)
Original Article from The New England Journal of Medicine — First-Line Nivolumab in Stage IV or Recurrent Non-Small-Cell Lung Cancer